The Role of Technological Knowledge in Student Engagement, Mediated by Self-Efficacy among Students at High School X - Dina Maria; Vira Arini Ridwan; Febrianis Virlita; Rilla Sovitriana (Journal of Islamic Psychology and Behavioral Sciences, 2026)
This study aims to examine and analyze the role of technological knowledge on student engagement mediated by self-efficacy among students of Senior High School X. Technological knowledge refers to an individual’s proficiency in understanding and utilizing various information technologies to accomplish tasks. Student engagement is described as the level of student’s participation in learning and teaching activities that lead to student’s learning outcomes and goals. Self-efficacy is defined as an individual’s belief in their ability to achieve desired goals. A total of 270 students participated in this study. The sampling technique used was non-probability sampling with a random sampling method. Multiple regression analysis was conducted to examine the relationships among variables. The results indicated that self-efficacy partially mediates the role of technological knowledge on student engagement. Based on the comparative analysis, younger students were found to have higher average levels of technological knowledge and student engagement compared to older students. Additionally, tenth-grade students demonstrated higher average levels of technological knowledge, self-efficacy, and two dimensions of student engagement. Furthermore, students who chose online learning showed higher average levels of technological knowledge and self-efficacy, while students who chose hybrid learning demonstrated higher emotional engagement.